The GABAB receptor agonist baclofen inhibits the reconsolidation of methamphetamine reward memory in adolescent and adult REM sleep-deprived rats - Müller, Christian P.; Khodamoradi, Mehdi (Progress in neuro-psychopharmacology & biological psychiatry, 2025)
Methamphetamine (METH) is a highly addictive psychostimulant drug. A key behavior of addiction is the relapse to drug-seeking and self-administration after abstinence. Like small amounts of a drug, does sleep deprivation increase the risk of relapse. Thus, identifying the mechanisms of relapse, and inhibiting them, is one strategy to develop a better treatment of addiction. In this study, adolescent and adult male rats underwent a 7-day episode of REM sleep deprivation (RSD). Following this, they were trained to establish a METH (2 mg/kg, i.p.)-induced conditioned place preference (CPP). After CPP extinction, rats received a memory reactivation session to trigger METH-CPP reinstatement. Immediately after this session, they received the GABAB receptor (GABAB-R) agonist baclofen (0, 2.5, or 5 mg/kg, i.p.). The results showed that baclofen, administered during the reconsolidation phase of METH CPP, significantly reduced METH reinstatement in both adolescent and adult rats in a dose-dependent manner. In adolescent rats, RSD enhanced METH reward memory, while it had no effect on adult rats. Although baclofen consistently reduced METH reinstatement in RSD adolescent rats, this effect was not observed in RSD adult rats. Furthermore, RSD increased GABAB-R1 subunit expression in the prefrontal cortex of both age groups. However, baclofen did not affect GABAB-R1 subunit expression in either group. These findings provide evidence for a role of the GABAB-R in METH memory reconsolidation across different ages, its vulnerability to RSD. They further support the potential of baclofen as a treatment for mitigating behaviors associated with METH abuse.
Gesehen am 02.02.2026